A IMPLEMENTATION OF LEARNING MODELS IN ISLAMIC RELIGIOUS EDUCATION IN THE DIGITAL ERA AT PASIRJAYA ELEMENTARY SCHOOL, TASIKMALAYA - Kosasih, Fitriani; Latip, Abdul; Pupu Maspupah; Rosmayati; Rosalia Ananta; Suhendar, Deni; Kurnia, Indra; Ahmad Syarif, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Islamic Religious Education (PAI) learning models in the digital era at SDN Pasirjaya Tasikmalaya. The research employs a descriptive qualitative approach with data collected through interviews, observation, and documentation involving PAI teachers, students, and the school principal. The findings reveal that PAI learning at SDN Pasirjaya has integrated digital platforms such as Google Classroom, Zoom, and interactive learning applications into instructional practice. Teachers serve not only as content deliverers but also as learning experience designers who craft adaptive, authentic, and meaningful learning encounters. The integration of Aswaja values within digital media usage ensures that learning remains grounded in moderate Islamic tradition. Three key models are identified: collaborative discussion, project-based learning (PjBL), and outcome-based education (OBE). Challenges include limited infrastructure, variable teacher digital competency, and inconsistent student motivation. The study proposes a framework for Islamic digital literacy as a new competency within PAI that encompasses academic, digital, and spiritual dimensions. These findings contribute a novel model for PAI learning in elementary schools in the digital age.